SCREENING OF GERMPLASM LINES AGAINST SAFFLOWER WILT CAUSED BY FUSARIUM OXYSPORUM F. SP. CARTHAMI - C. NARENDRA REDDY; S.TRIVENI, M. RAJENDRAPRASAD, B. VIDYA SAGAR, G. UMA DEVI (The Journal of Research, PJTSAU, 2022)
Safflower (Carthamus tinctorius L.) occupiesÂ prominent place in the agricultural wealth and economyÂ of India. It belongs to family Compositae and believes to be native of Afghanistan. The word Carthamus isÂ arabic word quartum (means the colour of dye obtainedÂ from florets). It is described as â€œKusumbhaâ€ in ancientÂ Sanskrit literature. Other Indian names, like Kusum,Â Karrad (Hindi), Kusumpuli (Bengali), KusumboÂ (Gujrathi), Kardi, Kurdi (Marathi), Sendurakam (Tamil),Â Kusuma (Telgu), Kusube, Kusume (Kannada),Â Kusumba (Punjabi) seem to have been derived fromÂ â€œKusumbhaâ€. Present the most common name beingÂ â€œKusumâ€ or â€œKardiâ€. It is a rich source of proteins andÂ edible oil and so many farmers plant it.